Exploring Interest Rate Models: Implications on Bond Value Measures in a Dynamic Financial Landscape - Suharto, Istiqomah; Yuningsih, Siti Hadiaty (iora, 2024)
This paper investigates the impact of various one-factor no-arbitrage interest rate models on key bond value measures, specifically effective duration. Employing numerical methods based on binomial or trinomial lattices, the study assesses five prominent interest rate models: Ho and Lee, Kalotay, Williams, and Fabozzi, Black, Derman, and Toy, Hull and White, and Black and Karasinski.The analysis begins by outlining the theoretical foundations and assumptions underlying each model, highlighting their distinctive features and implications for bond valuation. Through a meticulous numerical solution process, the study generates risk metrics for bond portfolios, considering the dynamic nature of interest rates and the complex interactions between price, duration, and convexity.Comparisons across the models reveal nuanced differences in the computed effective duration and convexity measures, shedding light on how the choice of an interest rate model may influence risk assessments in fixed-income portfolios. The paper discusses practical implications for investors and portfolio managers, emphasizing the importance of model selection in navigating the challenges posed by interest rate fluctuations. Additionally, it addresses the potential limitations and challenges associated with each model, offering insights into their relative strengths and weaknesses.By presenting empirical examples and conducting sensitivity analyses, this research contributes to the ongoing discourse on interest rate modeling and its implications for bond markets. The findings offer valuable insights for practitioners seeking to enhance their risk management strategies in fixed-income investments, providing a foundation for future research in this dynamic and evolving field.